ANALYSIS OF PACKAGING ELEMENTS AND ITS IMPACT TO CONSUMERS BUYING DECISIONS USING FACTOR ANALYSIS TOOL ON COFFEE PACKAGING PRODUCTS - Mohede, Christian Elroy; Tumbuan, W.J.F Alfa; Tielung, Maria V.J (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: The appearance of the package plays a significant role in influencing consumers or to stir up buying desire as the packages give out images or ideas to consumers and create emotional attachment in consumers towards the products. The main purpose of this research is to analyze the packaging elements and its impact to consumers buying decisions on coffee packaging. Factor Analysis method was used in this research and the types of this research is qualitative method. 100 respondents are contributed on this research. There are three findings in this research, which are The Aesthetic of packaging, second is the Protection and Environmental of Packaging, and Promotion. The recommendations that can be drawn in this research. Companies must carefully in choosing right color on the packaging, different packaging sizes based on consumers needs, shape of packaging must attractive, convenience in handling, improve the durability of packaging, a package that has no trouble on environment (friendly packages to environment). improve the design of packaging be attractive and unique, improve the bonus pack on packaging such a buy one get one to increase the consumers on coffee packaging. improve marketing strategies, consumers buying decisions were motivated by discount that listed on the packaging.Keywords: consumers buying decisions, factor analysis, packaging element, coffee packaging